2017
DOI: 10.1063/1.4997694
|View full text |Cite
|
Sign up to set email alerts
|

An improved sliding mode controller for a multifunctional photovoltaic grid tied inverter

Abstract: This paper proposes a robust control algorithm for a photovoltaic (PV) multifunctional grid tied inverter (MFGTI). The MFGTI is used to simultaneously inject the active power of a PV panel and enhance the power quality of a microgrid. The proposed algorithm will estimate the positive fundamental component of the source current even under strongly disturbed main voltage and load conditions. First, a Sliding Mode Controller is used to estimate the magnitude of the source current. Then, a positive fundamental com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In this work, the direct method has been adopted as shown in Figure 2 [2]. There are three blocks for this control strategy.…”
Section: Reference Current Generation Using the Direct Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the direct method has been adopted as shown in Figure 2 [2]. There are three blocks for this control strategy.…”
Section: Reference Current Generation Using the Direct Methodsmentioning
confidence: 99%
“…To this end, many identifications have been reported in the literature [9]- [22]; they [20], the nonlinear least square [21]. However, these techniques require a computational demanding, and its estimation accuracy is affected by the choice of sampling frequency and window length, the time-domain techniques such as the instantaneous power theory (IPT) [4], the diphase current method (DQ) and the direct [2], [22].…”
Section: Introductionmentioning
confidence: 99%
“…A. Safa et al [4] This article offers a robust control algorithm for Grid Connected Multifunctional Inverter (MFGTI) for Photovoltaic (PV). The MFGTI is used to simultaneously supply the active power of a photovoltaic module and improve the energy quality of a microgrid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The photovoltaic system is a potential renewable energy source with which it is possible to overcome dependence on fossil fuels [4]. Figure 1 shows the representation of a hybrid PV generation unit consisting of a PV generator, a DG, an inverter and a battery system.…”
Section: B Pv Module Modelingmentioning
confidence: 99%
“…Multi‐functional GCIs are gaining significant importance because of their capabilities to compensate harmonics, reactive power, unbalance, and neutral currents along with active power injection to the distribution system. The detailed review of the state of the art on multi‐functional GCI topologies and control strategies reported in the literature have been described in detail with its contributions and the research gaps in Table 1 11‐39 . All previously mentioned research studies discussed in Table 1 demonstrated their efficacy and legitimacy.…”
Section: Introductionmentioning
confidence: 99%